(untitled) (Al-Aasar, 2024)
Climate change is a global challenge that affects not only environmental issues but also economic, social, and governance aspects. This paper sheds light on the interdisciplinary approach that explores the links between social sciences, economics, and environmental governance. The aim of this research is to integrate these different fields to make climate change policies more effective and comprehensive. In this paper, we will analyze various policy solutions that guide the resolution of the climate crisis through the collaboration of these sectors